Layanan Supervisi Klinis Terhadap Pembelajaran Bahasa Arab di Madrasah Aliyah - Syahrial Labaso; Ratna Hestiana; Rinaldy, Asfar; Adtman A. Hasan (Faculty of Education and Teacher Training, 2024)
The role of educators in the learning process is crucial in determining educational quality, necessitating the enhancement of their capacities and competencies. Clinical supervision is a unique approach in educational supervision that focuses on empowering educators to remain relevant to curriculum guidelines while addressing students' learning needs. This method involves engaging educators in discussions to identify their weaknesses in the teaching process and guiding them towards solutions. This qualitative-descriptive study, utilizing interviews, observations, and documentation, examines the implementation of clinical supervision in Arabic language teaching at Madrasah Aliyah Muhammadiyah Kabila. The results indicate that clinical supervision helps educators formulate learning processes that stimulate student interest and encourage active participation. Arabic language instruction at the school employs both traditional and modern approaches. The traditional approach forms students' basic cognitive skills, while the modern approach applies these skills to everyday situations such as verbal communication and information technology use. Clinical supervision in Arabic language teaching is seen as bridging the gap between educators' psychological conditions and students' psychological readiness in the learning process. This approach proves effective in enhancing the quality of Arabic language instruction and student engagement.